2021
DOI: 10.1126/sciadv.abe1833
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of recurrent processing for figure-ground perception in mice

Abstract: The segregation of figures from the background is an important step in visual perception. In primary visual cortex, figures evoke stronger activity than backgrounds during a delayed phase of the neuronal responses, but it is unknown how this figure-ground modulation (FGM) arises and whether it is necessary for perception. Here, we show, using optogenetic silencing in mice, that the delayed V1 response phase is necessary for figure-ground segregation. Neurons in higher visual areas also exhibit FGM and optogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 90 publications
6
82
3
Order By: Relevance
“…In conclusion, our results suggest that suppression of top-down influence with c-tDCS in A7 decreases neuronal activity in the V1 cortex, which is consistent with some of previous studies using neural imaging measurement 6 , 12 and some single-unit recording studies that report facilitatory top-down effects on most neurons in the V1 or low-level visual cortex 7 , 9 , 33 , 41 , and is also supported by neuronal tracing studies that identify most feedback neurons as excitatory cells 43 , 44 although top-down modulation may mediated by a mechanism of disinhibition 41 . Our result is opposite to the results of other studies that report inhibitory top-down effects of V2/V3 cortex on V1 neurons in primate and mouse 8 , 29 , 32 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In conclusion, our results suggest that suppression of top-down influence with c-tDCS in A7 decreases neuronal activity in the V1 cortex, which is consistent with some of previous studies using neural imaging measurement 6 , 12 and some single-unit recording studies that report facilitatory top-down effects on most neurons in the V1 or low-level visual cortex 7 , 9 , 33 , 41 , and is also supported by neuronal tracing studies that identify most feedback neurons as excitatory cells 43 , 44 although top-down modulation may mediated by a mechanism of disinhibition 41 . Our result is opposite to the results of other studies that report inhibitory top-down effects of V2/V3 cortex on V1 neurons in primate and mouse 8 , 29 , 32 .…”
Section: Discussionsupporting
confidence: 92%
“…It is noteworthy that both the initial component (N1P1) and late component (P1N2) of VEPs in the V1 cortex were significantly affected by top-down suppression of A7. This is related to a recent debate about whether top-down influence can modulate the initial response of feedforward input to the V1 cortex 38 41 . Some authors report top-down facilitation effect on the late-phase neuronal response 41 or late ERP components (90–140 ms) 38 , whereas others find a strong attentional modulation on the initial response of VEP component (57 ms) and population response during the first wave of visual processing (< 100 ms) in the human V1 cortex 39 , 40 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, there are conditions for the circulation of impulses between neurons of higher and lower levels of afferent pathways. It has been experimentally confirmed that such oscillations occur [20][21][22][23][24].…”
Section: Theoretical Model Of Neuronal Circuits Realizing Perceptions Enabling the Memorization Of Images And Their Recall From Memory Inmentioning
confidence: 99%